Watt-level long-wave infrared CdSe pulsed-nanosecond optical parametric oscillator. (January 2022) - Yang, Ke; Li, Junhui; Gao, Yanzhao; Wei, Disheng; Yao, Baoquan; Wang, Jian; Cheng, Hongjuan; Tang, Jinwen; Mi, Shuyi; Duan, Xiaoming; Dai, Tongyu
Highlights: A rectangular ring cavity CdSe pulsed-nanosecond OPO output of 1.18-W average power at ~11 μm is reported. A linear cavity CdSe pulsed-nanosecond OPO output of 1.03-W average power at ~10.15 μm is reported. OPO is a promising method to obtain high average output power in the range 8–12 μm from a CdSe crystal. Before 2018, OPO was used to trying to obtain high average power in 8–12 μm from CdSe crystal. However, due to the low optical-to-optical conversion efficiency, the maximum average output power only reached 320 mW near 10 μm. Slowly, the OPO method tends to be abandoned. In 2020, the seed-injection method instead of OPO was used to achieve high average power output. Because of the fascinating simplicity and stability of the OPO method, we insisted on using OPO to achieve high power and succeeded in obtaining watt-level average power in 8–12 μm. Compared to previous OPO method, the improvement of average output power is about ~265%. Compared to seed-injection method, the the average output power improvement at 11 μm is about ~50%. For the first time, >1 W at ~11 μm laser was achieved. Therefore, OPO is still a promising method to obtain high average power 8–12 μm lasers. Abstract: In this paper, using two cadmium selenide (CdSe) crystals, we have demonstrated signal-resonant pulsed-nanosecond optical parametric oscillators (OPOs) in linear and rectangular ring cavity designs with output powers of up to 1.03 W at 10.15 μm (idler) and 1.18 W at 11 μm (idler) were obtained, respectively. A Q-switched Ho:YAG laser at 2.09 μm with a pulse repetition frequency of 1 kHz was used as the OPO pump source. At the maximum output power level of the idler at 10.15 μm, the corresponding slope efficiency and optical conversion efficiency were 5.22% and 2.33%, respectively, with a spatial beam quality of M 2  < 10.8. Similarly, we also recorded the slope efficiency and optical conversion efficiency at 11 μm to be around 5.38% and 2.73%, respectively, with a spatial beam quality of M 2  < 5.1. The idler wavelength is tunable in the 10.2–10.05-μm range for the linear cavity OPO with output power varying from 0.98 W at 10.2 μm to 1.09 W at 10.05 μm by varying the internal crystal angle from 72.7° to 73.39°. Similarly, the wavelength tunability of the idler was recorded to be 11.2–10.9 μm for the rectangular ring cavity OPO with output power varying from 1.04 W at 11.2 μm to 1.26 W at 10.9 μm by varying the internal crystal angle from 69.6° to 70.39°.